Slang Remaja Ghana di Kota Pahiang Provinsi Bengkulu (Suatu Kajian Sosiolinguistik) - Zulianti, Hajjah (Lentera: Jurnal Ilmiah Kependidikan, 2015)
This research entitled âSlang Remaja âGhanaâ di Kota Kepahiang Propoinsi Bengkulu Suatu Kajian Sosiolinguistikâ aimed to describe the slang expression form in Ghana community, to describe the forming of slang in Ghana community, to describe semantic meaning relation of slang in Ghana community, and to describe the function of using slang in Ghana community. This research is sociolinguistic research. In collecting the data, the researcher used listening method with recording technique, and interviewing method with noting technique. In analyzing the data, the researcher used correlation and distribution method. The result of the research is delivered informally. The result of the research showed that slang in Ghana community is in the form of word and phrase. The form of word is divided into five categories; those are noun, verb, adjective, pronoun, and numerals. Besides, the form of word is also divided into derivational word that includes reduplication. Slang in the form of phrase is divided into two categories; those are noun phrase and adjective phrase. There are three types of forming slang in Ghana community, (1) the forming of slang without any changed from the original words, (2) the forming of slang by using abbreviation, and (3) the forming of slang by using new words. The semantic meaning relation of slang in Ghana community is divided into five semantic meaning; those are synonymy, homonymy, polysemy, metaphor, and unidentified meaning of slang. There are five functions of using slang in Ghana community, (1) the using of slang for close relationship, (2) the using of slang for politeness or euphemism, (3) the using of slang for secrecy, (4) the using of slang for allusion and (5) the using of slang to express the feeling.